India: a new partner in democracy promotion? - Jörg Faust; Christian Wagner (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Unlike China and Russia, India is a democratic country, which could act as an important partner in international democracy promotion. Despite increasing requests from the United States and European governments, the promotion of democracy has not so far had a high priority in India's foreign policy. Indian elites are concerned about losing their role as spokesmen for developing countries in global affairs if the country abandons the principle of non-intervention in favour of democracy promotion. As links between India and most fragile South Asian states are closely related to problems of nationand state-building, Indian foreign policy-makers fear that active democracy promotion could weaken the country's regional position rather than strengthening it. Finally, there are concerns among political elites that active democracy promotion may backfire by triggering a domestic debate on the defects in Indian democracy–corruption and clientelism – as the main causes of social exclusion.
Keywords: 330